Training To Strengthen The Branding Of Muhammadiyah Schools At Mi Muhammadiyah 3 Dukuh – Wuluhan - Rofi, Sofyan; Herlambang, Toni; Kusumawati, Dahani (Journal Of Humanities Community Empowerment, 2025)
Relating to one type of educational institution, namely schools, currently there are still many schools/madrasas that have difficulty accepting new students, which has an impact on the minimum number of students entering these schools/madrasas. This phenomenon cannot be separated from the growth of new educational institutions, as well as changes in government policy in accepting new students for state schools such as zoning pathways, achievement pathways, independent pathways and other pathways. This has an impact on the ability of private schools/madrasahs in villages in particular, to become a destination or choice for prospective new students to receive education. Based on this, strategies are needed to increase public interest in schools or institutions. The strategy is "School Branding". School branding in offering its institution to prospective students. The concept of school branding is related to brand image, namely as an image displayed by schools/madrasahs to potential customers, namely students and parents (Rizkiyah et al., 2020). The image of the school/madrasah must be able to be displayed in a straightforward and firm manner as a supporting factor in the process of accepting new students, so that they are interested in registering at the school/madrasah. So to develop this strategy, training is needed to build the school's image